Optimising Village Financial Management through the Implementation of Accounting Information Systems: A Case Study in Jayapura City - Siahay, Adolf Z. D. (Amkop Management Accounting Review (AMAR), 2025)
Village financial management is an essential aspect of realising transparent and accountable governance. However, many villages still face obstacles in financial reporting and accounting due to limited information systems. This study was conducted to analyse the effect of the implementation of an accounting information system on village financial management in Jayapura City. This study used a quantitative, explanatory approach to examine the cause-and-effect relationship between variables. The research population included financial management officials from all villages in Jayapura City. The sampling technique used was purposive sampling, with 140 respondents comprising village heads, village secretaries, treasurers, and heads of financial affairs. Data were collected using questionnaires and analysed using Partial Least Squares – Structural Equation Modelling (PLS-SEM) in SmartPLS version 4. The results showed that the implementation of accounting information systems had a positive and significant effect on village financial management. The application of technology-based information systems was proven to increase the transparency, efficiency, and accountability of village fund management. This study has theoretical implications for strengthening the Information System Success Model and practical implications for local governments in expanding the digitisation of village financial systems to enhance good-governance-based administration.